MODIFICATION OF SCREEN PRINTED CARBON ELECTRODE (SPCE) WITH AG/MIL-101(FE) FOR DOPAMINE DETECTION - Permata Sari, Sunarseh
Material Institute Lavoisier (MIL-101(Fe)) is a type of Metal Organic Framework (MOF) consisting of iron(III) ions that coordinate with terephthalic acid as a linker. A Screen Printed Carbon Electrode (SPCE) modified with MIL-101(Fe) and Ag nanoparticles was fabricated to detect dopamine. Ag nanoparticles are used enhance the sensitivity of the sensor to dopamine (DA). MIL-101(Fe) was synthesized using the hydrothermal method, and Ag synthesis in MIL-101(Fe) used the reduction method with NaBH4 as a reducing agent. Ag/MIL-101(Fe) was characterized by FTIR, SEM-EDX, and XRD. The modification of Ag/MIL-101(Fe) was carried out using the drop casting method on the surface of the SPCE working electrode. Optimization of Ag/MIL-101(Fe) measurements was performed on DA, and the optimum DA measurements were at pH 6.5, material concentration 2 mg/mL. The SPCE with Ag/MIL-101(Fe) modification showed a good response to DA (Ipa= 32.32 µA, Epa= 0.1948), and the reaction mechanism that occurs on the electrode surface is controlled by a diffusion process. The measurement of 500 µM DA in Phosphate Buffer Saline (PBS) was carried out using the DPV measurement technique with a potential range of -0.30 to 0.75 V and a scan rate of 10 mV. The calibration curve shows the linear range of DA measurements, namely 0.1-300 µM, and a detection limit of 0.08 µM. The modified electrodes were used to detect DA in urine and compared with a UV spectrophotometer. The sensor that was successfully created detected DA in urine with a recovery percentage of 96,64% and 97,07%. The sensor has the potential to be applied in the pharmacological and analytical fields because it has good sensitivity, selectivity, and reproducibility.